Predictive value of left ventricular dyssynchrony for short-term outcomes in three-vessel disease patients undergoing coronary artery bypass grafting with preserved or mildly reduced left ventricular ejection fraction - Liu, Jia; Fan, Rui; Li, Cui-ling; Liu, Yan-qiu; Liu, Dong-hong; Li, Wei; Yao, Feng-juan (Frontiers in Cardiovascular Medicine, 2022)
Background and Objective: Coronary artery bypass grafting (CABG) is the reference standard intervention in coronary artery disease (CAD) patients with three-vessel disease (3VD). We aimed to evaluate the predictive value of left ventricular (LV) dyssynchrony for short-term adverse outcomes in patients with 3VD undergoing CABG with preserved or mildly reduced LV ejection fraction (LVEF). Methods: This study involved ninety-five 3VD patients with preserved or mildly reduced LVEF undergoing scheduled on-pump CABG. The preoperative diameters and volumes of LV and LVEF were obtained by two-dimensional echocardiography. LV dyssynchrony parameters were acquired by real-time three-dimensional echocardiography (RT-3DE) and analyzed by HeartModel quantification software. And the perfusion index of LV was obtained by contrast echocardiography. The clinical endpoints of short-term adverse outcomes comprised 30-day mortality and/or composite outcomes of postoperative complications. Univariate and multivariate logistic regression analyses were used to identify risk factors for the occurrence of post-CABG short-term adverse outcomes. Results: Short-term adverse outcomes occurred in 12 (12.6%) patients. These patients had higher LV dyssynchrony parameters obtained through RT-3DE. The standard deviation of the time to minimum systolic volume corrected by heart rate over 16 segments (Tmsv16-SD%) [odds ratio, 1.362; 95% confidence interval (1.090-1.702); P = 0.006], one of the LV dyssynchrony parameters, was independently associated with short-term adverse outcomes. Patients with poor synchronization tended to spend more time in the intensive care unit and hospital after surgery. Conclusions: Preoperative LV dyssynchrony parameter Tmsv16-SD% obtained through RT-3DE could be a useful additional predictor of postoperative short-term adverse outcomes in 3VD patients with preserved or mildly reduced LVEF undergoing CABG.